Obesity in Children: Frequency of Occurrence and Features of Thickness of Epicardial Fat Depending on Indicators of Body Weight Index and Lipid Spectrum - Shoira Abdusalamovna, Agzamova; Guzaliya Marsovna , Hasanova (International Journal of Psychosocial Rehabilitation, 2020)
The article provides information on recent scientific studies of the relationship of visceral obesity with complications from the cardiovascular system. The results of our own research on the frequency of occurrence of overweight and obesity among teenage schoolchildren of one of the schools in the city of Tashkent are presented, as well as data on the assessment of the lipid spectrum, echocardiographic studies of the structural state of the myocardium, and identification of epicardial fat in overweight adolescents and exogenously constitutional obesity of the 1st degree.